The reinvention of Turin's image. A New identity between economic uncertainty and social issues. - Pede, Elena; Rossignolo, Cristiana; Caruso, Nadia (Taylor & Francis, 2019)
Over the decades, Turin has dealt with periodic social and economic crises, continuously questioning itself in terms of its future and identity since the 1950s, the City has distinguished itself as a one-company town in the automotive sector. However, the collapse of the Fordist model in the 1970s led to a rapid reversal of the city's fortunes. Since then, efforts have been made to restructure the economic urban agenda and rethink urban development. With the 2006 Winter Olympic Games the worst seemed to be over, but just two years later, the world financial crisis hit the city even harder.
Keywords: Stadtentwicklung; Stadtplanung; Entwicklungsziel; Masterplan; Krise; Automobilindustrie; Industriestadt; Transformation; Strukturwandel; Wissensgesellschaft; Event; Großprojekt; Tourismus